Selenium supplementation levels and sources in post-larvae Nile tilapia diet - João Marcos Monteiro Batista; Leonardo Augusto Fonseca Pascoal; José Humberto Vilar da Silva; Veruska Dilyanne Silva Gomes; Alda Lúcia de Lima Amâncio; Ricardo Romão Guerra; Jorge Luiz Santos de Almeida; Chimenes Darlan Leal de Araújo; Jonathan Mádson dos Santos Almeida; Jairo Janailton Alves dos Santos (Semina: Ciências Agrárias, 2022)
Fish larviculture exert great influence in the subsequent phases, in which nutrition is a basic prerequisite for success. Therefore, when it is in an intensified production system, it promotes the limitation of some minerals, making it necessary to supplement selenium in diets for post-larvae. The objective of this study was to evaluate selenium levels and sources in post-larvae Nile tilapia diets on muscle performance and histology. A total of 1,260 post-larvae with an initial average weight of 0.010 g were used, distributed in a completely randomized design in a factorial scheme with four supplementation levels (0.6; 0.9; 1.2 and 1.5 mg of Se/Kg) and two sources (sodium selenite and selenium yeast), plus the negative control, with 35 post-larvae Nile tilapia used per experimental unit. The physical-chemical parameters of water quality were within those recommended for tilapia cultivation. Feed consumption (p < 0.05) and hepatosomatic index (p < 0.05) were affected by the source used. Effects of supplemented selenium levels and sources were not observed for the other performance variables. Higher values for final height, final width, specific development rate and protein efficiency rate were found (p < 0.05) when comparing the control diet with diets containing the sodium selenite source. No effects on muscle fiber morphometry were observed (p > 0.05) in the studied variables. It is concluded that 0.6 mg of selenium in the diet, regardless of the source used, met the mineral requirement for post-larvae Nile tilapia.